PROTECTING STUDENTS WORLDVIEW FROM NEGATIVE PERCEPTIONS RELATED TO CORRUPTION - Surat Botir o‘g‘li , Ravshanov (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to develop educational strategies that cultivate an anti-corruption worldview and foster ethical consciousness among students in Uzbekistan by integrating civic education, interactive learning, and national moral philosophy. Method: Using a qualitative-descriptive approach, the research analyzes pedagogical practices, curricular elements, and national initiatives such as “Honesty Lessons,” supported by textual analysis of works by prominent Uzbek thinkers including Alisher Navoi, Abdulla Avloniy, and Mahmudhoja Behbudiy. Results: The findings reveal that role-playing, value-based competitions, transparent assessment methods, and community engagement significantly enhance students’ moral awareness, critical thinking, and civic responsibility. Teachers and institutional support systems play a pivotal role in reinforcing these values through practical and contextualized learning experiences. Novelty: This study introduces a culturally grounded, age-appropriate framework for anti-corruption education that uniquely combines classical Uzbek philosophical thought with contemporary pedagogical methods. It fills a gap in the literature by proposing a structured, context-specific model aimed at instilling integrity and resistance to corruption in school-aged learners within a Central Asian context.